Taxonomy of the Mexican species of Belonuchus Nordmann (Coleoptera: Staphylinidae) - Márquez, Juan; Asiain, Julieta (Zootaxa, 2022)
Belonuchus is a diverse genus in the subtribe Philonthina (subfamily Staphylininae, tribe Staphylinini), with some of its species being frequently collected. For the majority of the Mexican species of Belonuchus, little or no taxonomic information has been reported after their original description. For this reason, the Mexican species of Belonuchus were taxonomically revised based on the study of specimens deposited in several Mexican and international collections. We propose eight species groups to accommodate the Mexican species, five of them supported by one unique diagnostic character. Keys to species groups and species in each group, together with photos and drawings of diagnostic structures, are included. Redescriptions of the 29 known species, descriptions of 16 new species, with information about intraspecific variation in terms of secondary sexual dimorphism and size, two new country records (Mexico and Guatemala) and 26 new state records are also included. We propose B. xanthopus Solsky, 1868 and B. celatus (Sharp, 1885) as new synonyms of B. connexus (Say, 1830); B. iteratus (Sharp, 1887) as a new synonym of B. xanthomelas Solsky, 1868; B. latecinctus (Sharp, 1885) as a new synonym of B. iridescens Solsky, 1868; and B. mexicanus Solsky, 1864 as a new synonym of B. viridipennis Baudi di Selve, 1848. Lectotypes were designated for: Belonuchus cariniventris Bernhauer, 1918; Philonthus trochanterinus Sharp, 1885; Philonthus zunilensis Sharp, 1885; Belonuchus jalappensis Bernhauer, 1917; Philonthus iteratus Sharp, 1887; Belonuchus nigerrimus Bernhauer, 1918; and Belonuchus pectinipes Bernhauer, 1910. The Mexican species of Belonuchus are mostly recorded from cloud forest (60%), oak forest (51.1%) and oak-pine forest (46.6%).